2016
DOI: 10.1002/pi.5145
|View full text |Cite
|
Sign up to set email alerts
|

High performance poly(N‐aryleneindole ether) containing pyridine units as a novel acid response fluorescent detector

Abstract: A novel high-performance polyindole containing a pyridine ring (P1) was successfully prepared by the catalyst-free nucleophilic substitution polycondensation of 4-hydroxyindole with 2,6-difluoropyridine via a C − N and C − O coupling reaction process. This semirigid polyindole P1 exhibits good thermal stability, and it can be dissolved well in common organic solvents. Fluorescent spectral studies indicate that the resulting polymer shows blue-light emission at 402 nm due to the effect of intramolecular charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The target compound was prepared following the general procedure in 7,137.2,131.7,131.3,131.2 (d,J = 6.0 Hz),131.1,128.5,128.1,126.9,122.3,120.3,119.3,115 The target compound was prepared following the general procedure in Table 2 137.3, 133.8, 131.6, 131.2, 131.1, 131.0, 128.5, 128.4, 128.3, 126.7, 122.4, 120.4, 119.3, 113.9, 109.7, 31.0.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The target compound was prepared following the general procedure in 7,137.2,131.7,131.3,131.2 (d,J = 6.0 Hz),131.1,128.5,128.1,126.9,122.3,120.3,119.3,115 The target compound was prepared following the general procedure in Table 2 137.3, 133.8, 131.6, 131.2, 131.1, 131.0, 128.5, 128.4, 128.3, 126.7, 122.4, 120.4, 119.3, 113.9, 109.7, 31.0.…”
Section: Organic and Biomolecular Chemistry Papermentioning
confidence: 99%
“…3 Indole moieties are commonly found in bioactive substances, 4 electronic materials, 5 optically responsive materials, 6 and fluorescent polymer sensors. 7 As a result of their outstanding bio-significant and commercial applications, substituted indoles have received considerable attention from the scientific community. In the biological significance of indole molecules, the antiviral properties of arbidol 8 a and lescol have been recognized for HMG-CoA-reductase inhibition properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 Indole moieties are common in bioactive substances, 2 optically responsive materials, 3 electronic materials, 4 and uorescent polymer sensors. 5 Many methods for the synthesis of indole derivatives have been developed. [6][7][8][9][10][11][12][13][14][15][16] Fischer and co-workers reported that the reactions of aryl hydrazines with ketones gave 2,3-disubstituted indoles.…”
Section: Introductionmentioning
confidence: 99%
“…The diazocine group serves as a cyclooctatetraene analogy which has a nonplanar 8‐membered ring structure with nitrogen atoms as shown in the Figure A. According to the literature precedent, diazocine which has lone pair electrons is easily bind with protons to form diazocinium ,. In addition, the diazocinium unit is a strong electron‐accepting group and exhibits a stronger intra molecular charge transfer (ICT) effect.…”
Section: Introductionmentioning
confidence: 99%